Unmanned Aircraft System traffic management: Concept of operation and system architecture - Tao Jiang; Jared Geller; Daiheng Ni; John Collura (International Journal of Transportation Science and Technology, 2016)
Within the past few years, civilian demand for small unmanned aircraft systems (sUAS), commonly referred to as drones, has skyrocketed. The passage of the Federal Aviation Administration (FAA) Modernization and Reform Act in 2012 acknowledged this fact, and has since prompted expedited research and development for civilian sUAS. As proposed at a recent National Aeronautics and Space Administration (NASA) Convention, central to the safe and efficient operations of sUAS will be an unmanned aircraft system traffic management (UTM) system. Such a UTM system will borrow fundamental ideas from large-scale air-traffic control, albeit with several key differences that provide for sUAS which vary in method of control, maneuverability, function, range, and operational constraints. Ultimately, an expansion of UTM infrastructure, a decentralization of governing authority over sUAS operations, and the establishment of a web-interface for pilots to submit flight plans and access crucial data will allow for sUAS operations to shift from being a science-fiction gimmick to an element of daily life. The major objectives of this paper are to: (1) define what a UTM system is; (2) review current UTM practice from industry partners; (3) describe how sUAS pilots would use a typical UTM system, and who has authority over UTM; and (4) determine what physical architecture is required in a UTM system which handles a large variety of sUAS.